2014
DOI: 10.1021/am506272c
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Controlled ZnO Nanowire Arrays for Tailored Hybrid Composites with High Damping

Abstract: Hybrid fiber reinforced composites using a nanoscale reinforcement of the interface have not reached their optimal performance in practical applications due to their complex design and the challenging assembly of their multiscale components. One promising approach to the fabrication of hybrid composites is the growth of zinc oxide (ZnO) nanowire arrays on the surface of carbon fibers to provide improved interfacial strength and out of plane reinforcement. However, this approach has been demonstrated mainly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…In previous experimental and analytical studies, it was shown that the growth of vertically aligned ZnO nanowires on carbon fiber led to improvements of interfacial shear strength as well as enhanced energy dissipation [20][21][22][23][24][25]. The strong nanowire interface is created through increased surface area, which is advantageous for van der Waals bonding, and strengthened mechanical interlocking between the nanowires and epoxy matrix [23].…”
Section: Introductionmentioning
confidence: 99%
“…In previous experimental and analytical studies, it was shown that the growth of vertically aligned ZnO nanowires on carbon fiber led to improvements of interfacial shear strength as well as enhanced energy dissipation [20][21][22][23][24][25]. The strong nanowire interface is created through increased surface area, which is advantageous for van der Waals bonding, and strengthened mechanical interlocking between the nanowires and epoxy matrix [23].…”
Section: Introductionmentioning
confidence: 99%
“…For another thing, micro-turbulent flow around the wire complicates the interaction on the solution/substrate interface, resulting in enlarged defects [22]. Furthermore, most studies on wetprocess growth of longer oxide nanowire were based on repeated batch-type hydrothermal reaction [23,24]. To provide better optimization for the device structure, the ZnO growth process should be finely controlled continuously, aiming to synthesize wellaligned array of nanowires with continuously-adjustable length and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…This is of importance in modelling the contact of soft biological tissues such as, muscles, skin and brainstem. Mechanical properties of the novel composites can be controlled and tuned by morphology, distribution and alignment processes to achieve the desired characteristics [21]. Moreover, fiber reinforced composites can (depending on the direction of the fibers in the composite) show transversely isotropic characteristics.…”
Section: Introductionmentioning
confidence: 99%